PENERAPAN BASIS DATA DALAM TRACER STUDY - Rachmat Hidayat; Dina Hermina (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The management of alumni data and low alumni participation constitute significant obstacles to curriculum evaluation and the fulfillment of IAPS 4.0 accreditation criteria. The proposed solution is the implementation of a Web-Based E-Tracer Study Application designed using the Model–View–Controller (MVC) architecture and supported by a database to integrate and manage data in a centralized manner. The database plays a crucial role as it enables data processing using Data Mining techniques (such as the Apriori algorithm or hash-based methods) to discover strategic association patterns between graduate competencies and job performance. The implementation of this system is able to significantly increase alumni participation rates (reaching over 90% compared to 20% using manual methods). However, sustainable success requires addressing non-technical challenges, such as low emotional attachment among alumni, through integrated solutions including automated reminder features and enhanced data security (multi-level authentication and encryption). Overall, database integration has proven effective in transforming graduate data into objective and strategic feedback to improve educational quality and alumni competitiveness.